Comparison Of Prenatal Attachment Between Primigravida And Multigravida Mothers (HEALTH CARE: JURNAL KESEHATAN, 2025)
Prenatal attachment refers to the emotional bond that forms between mothers and their unborn babies during pregnancy. parity is one of the factors that influence the level of prenatal attachment in mothers. The aim of this study was to compare prenatal attachment between primigravida and multigravida mothers at a Health Center in Pekanbaru City in 2024. This study employed a comparative descriptive research design with a cross-sectional approach. The research was conducted at the Health Center with the highest number of pregnant women in Pekanbaru City, according to data from the Health Office in 2023. The study sample consisted of 104 pregnant women, including 52 primigravida and 52 multigravida, selected using a purposive sampling technique. The Indonesian Version of the Prenatal Attachment Inventory (IPAI) questionnaire, a Likert scale with scores ≤ 52 (low) and > 52 (high), was used to assess prenatal attachment. The findings revealed a significant difference in prenatal attachment levels between the primigravida and multigravida groups (p-value 0.032 < α 0.05). The mean prenatal attachment score was notably higher in the primigravida group (58.85) compared to the multigravida group (46.15), with a difference of 12.7 points in favor of the primigravida group.